An innovation and transformation of organic sheet masks from black cumin extract (Nigella Sativa L.) / Alivia Rianti Putri ... [et al.] - Putri, Alivia Rianti; Rahayu, Della Sinta; Chaerani, Ayu Dyah; Anggraeni, Sekar; Santoso, Muhammad Ragil; Mozhaib, Syachpattila Maulana (2022)
Facial skin care processes have basically undergone various types of innovations and transformations that have rapid development in the world of skincare. As it is known that face skin is quite sensitive for the most, including the women who carry out periodic maintenance. By using a sheet mask, it is hoped that it will be able to prevent skin aging. Meanwhile, the purpose of the research is to innovate a sheet mask made from the basic material of Black Cumin (Nigella Sativa L.) which has the property to disguise black spots and as an antioxidant on the face by taking the result of the extraction process. In addition, there is an additional Glycerin as the main raw material in making sheet mask extract which has properties to moisturize facial skin in a structured manner. To get the maximum result, this study also refers to the method of literature – the previous literature related to an innovation of black cumin extract for sheet masks.